A case study of imported pulmonary coccidioidomycosis - Wang, Zheng-yang (Zhejiang University Press, 2011)
Coccidioidomycosis is an endemic disease of the Western hemisphere. The cases in non-endemic areas are mostly imported. Determining a history of exposure is critical for performing the diagnosis of coccidioidomycosis, especially for cases occurring in a non-endemic area. In this study, a 71-year-old Chinese male presented to our hospital with chronic cough and malaise, and was found to have a mass in the middle lobe of right lung. He had been visiting Arizona, USA for four months before admission. Pulmonary coccidioidomycosis was confirmed by the results of histopathological examination after lobectomy. Typical microscopic features of Coccidioides are definitely diagnostic, but need be differentiated from other budding yeast infection or carcinoma histopathologically.